Piscine predation rates vary relative to habitat, but not protected status, in an island chain with an established marine reserve - Kough, Andrew S.; Belak, Carolyn A. (Frontiers in Marine Science, 2022)
Establishing marine reserves can increase biomass and diversity relative to surrounding areas. However, such changes presumably alter species compositions, interactions, and associated demographic processes such as predation. We investigated relative predation pressure by fish inside and outside of a well-established no-take reserve using standardized predation tether units: Squidpops. We deployed Squidpops (N = 990) monitored by cameras to examine predation, as estimated by consumption rates, between paired seagrass and patch reef habitat sites proximate to the Exuma Cays Land and Sea Park, a well-enforced no-take Bahamian reserve since 1986. Surprisingly, there was no significant park effect on consumption nor observed diversity. Significantly higher consumption rates were found at patch reef sites relative to seagrass sites, occurred in association with higher fish diversity and with longer soak times. Observed fish diversity was predicted by habitat and distance inshore with more species found on patch reefs and further from the deep water Exuma Sound. Recorded fish bites were positively associated with patch reef habitat, with reef dwelling fish, and increased as the species became more commonly encountered. Deployment-specific factors, including temperature, depth, and time of day had little impact on measured predation, an expected result as the experiments occurred in similar locations over a fine temporal scale. In our experiment, ecosystem-based factors outweighed the place-based management effects that we expected from being within the oldest well-enforced no-take marine reserve in the Caribbean versus the surrounding actively fished waters. Despite well-documented increases in abundances across trophic levels from primary consumers to apex predators within the reserve, predation rates were not significantly different than adjacent areas. Evaluating the efficacy of a marine reserve in protecting vital ecosystem processes requires studies beyond abundance and diversity surveys. By focusing on predation on two of the most ubiquitous habitats throughout the region and on common species, rather than on exceptional sites and charismatic species, we reveal a process that seems relatively unchanged by strict marine conservation management.